Effect of Cornstover Char and Indigeneous Bacteria on the Physiochemical Properties and Hydrocarbon Degradation of Crude Oil - Contaminated soil - O. Ovie; L. E. Tudararo-Aherobo; A. C. Ibezute (Journal of Applied Sciences and Environmental Management)
Bioremediation offers a sustainable approach to addressing crude oil contamination in soil, leveraging microbial activity and nutrient amendments to enhance hydrocarbon degradation. Hence, the objective of this paper is to evaluate the effects of Cornstover char and indigenous Bacteria on the physiochemical properties and hydrocarbon degradation in crude oil-contaminated soil using appropriate standard procedures. Results revealed significant increases in pH, notably from 9.3 to 11.85 in the SCCC setup, while setups like SCCS showed a transient spike to 12.15 by Week 4 before stabilizing at 11.3. Electrical conductivity decreased significantly across most setups, such as SC, which dropped from 470 to 109.5 µS/cm, indicative of hydrocarbon breakdown and nutrient utilization. The SCCC and SCCN setups achieved the highest TPH degradation rates, 93.99% and 94.60%, respectively, while natural attenuation in SC showed a limited reduction of 49.28%. PAH degradation followed a similar trend, with SCCC and SCCN setups achieving 74.71% and 91.47% degradation, respectively. This study underscores the synergistic effects of microbial augmentation and nutrient supplementation in optimizing hydrocarbon degradation. The findings provide valuable insights for developing scalable, site-specific bioremediation strategies. Further exploration of long-term soil health and microbial dynamics is recommended to enhance bioremediation practices.